Relationship between vertical jumps and different slalom courses - Strojnik, V.; Dolenec, A. (Science and Skiing IV, 2008)
INTRODUCTION; Vertical jumps are highly standardized actions representing action of leg extensors in different contraction conditions: concentric, slow stretch-shortening cycle (SSC) and fast SSC action. Based on previous observation (not published) it was expected that different slalom courses will be related to different vertical jumps. This would reveal specific motor structure that may favor success in specific Slalom course and can be consequently used for conditioning preparation. The aim of the study was to analyze different slalom courses if they differ regarding typical contraction conditions assessed with vertical jumps.